Gender as Determinant of the Effect of Yeast Selenium on CD4 T Cells Count Among HIV 1 Positive Children - Otieno, Samwel Boaz (Journal of Cells, 2017)
Background Sex steroid estrogens (E2) have been observed to have synergistic effect on activity of GSH-px on pre-menopausal females taking selenium. GSH-px activity is correlated to CD4 T cell count in HIV positive patients. However no study has been done to determine gender differentiated effect of yeast selenium intake on CD4 T cell count of pre-puberty male and female children. Methods In the study 25 girls and 25 boys HIV-1 positive on WHO stage three and below were given 50μg yeast selenium and blood samples taken at zero, three and six months intervals in EDTA vacuutainers. The blood samples were analyzed for CD4 T cell count by ELISA. Results: No significant CD4 T cell count change in the test group = -2.943,p< 0.05 compared to the matched controls t = -1.258 p> 0.05. CD4 T cell count increased among all age groups on test 3-5years (+ 267.1),5-8 years( +200.3) 9-15 years (+71.2) cells/mm3 and while in matched controls there was a decrease in all age groups 3-5 years(-71),5-8 years (-125) and 9-13years(-10.1)cells/mm3 . No significant difference was observed in CD4 T cell count between boys and Girls F (df 5, 81) = 1.379 p=0.241 between girls F ( df 2,32) = 1.531, p= 0.232 and between boys F ( df 2, 49) = 1.040, p= 0.361 on selenium and between boys and girls F (df 5, 86) = 1.168, p= 0.332 on control at six months. Conclusion It can be concluded that there was significant increase in CD4 T cell count among the children on selenium, but no significant difference in the effect of selenium on CD4 T cell count between pre-menopausal females and male.